Enhancing Cationic Drug Delivery with Polymeric Carriers: The Coulomb‐pH Switch Approach. Issue 2 (21st December 2020) - De Luca, Sergio; Treny, Jennifer; Chen, Fan; Seal, Prasenjit; Stenzel, Martina H.; Smith, Sean C.
Abstract: A new coulomb‐pH switch method is proposed to enhance the efficient release of cationic drugs under acidic conditions occurring near tumor cells or during uptake into cells via endocytosis. The strategy is based on incorporation into the polymeric carrier of both weak acid and weak base functionalities. The consequence of this new design is that the polymeric vector adopts negative charge at physiological pH—facilitating complexation—while at late endosomal pH of 4.5, the polymeric vector adopts a positive charge—promoting highly efficient release of the drug. To illustrate the strategy, molecular dynamics simulations are carried out for a representative system comprising of a peptide dendrimer Gly‐Lys(Arg)2 as a model cationic drug and a short poly(4‐vinyl imidazole)‐b poly(acrylic acid) (PVI‐b‐PAA) block co‐polymer vector. Simulations suggest that these coulomb‐pH switch vectors bind the cationic drug effectively at pH = 7.0 and release it decisively once the charge state is changed to reflect pH = 4.5, as indicated by hydrogen bonding, close contact, and distance correlation analyses. Complementary experiments with bespoke synthesized peptide dendrimers indicate that the complexation involves much larger aggregrates than the one‐to‐one simulation; however unambiguous evidence is provided for the dissolution of the aggregates at pH = 4.5. Abstract : This work proposes a new coulomb‐pH switch method to enhance the efficient release of cationic drugs under acidic conditions occurring near tumor cells or during uptake into cells via endocytosis. Molecular dynamics and complimentary experiments of drug/carrier complexation demonstrate that the carriers bind the cationic drug effectively at pH = 7.0 and release it decisively at pH = 4.5.